Sansho the bailiff [videorecording (DVD)] - Mizoguchi, Kenji, 1898-1956; Tanaka, Kinuyo, 1909-1977; Hanayagi, Yoshiaki, 1924-1978; Kagawa, Kyōko; Mori, Ogai, 1862-1922 (Criterion collection (DVD videodiscs), 2015)
Slave traders tear a governer's family apart after a feudal lord forces him into exile.